PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS X MIPA SMA NEGERI 2 PADANG - Sarifa Aini (Departemen Matematika, 2019)
Mathematical problem solving ability of students of class X MIPA SMA Negeri 2 Padang were low. The causes were the application of learning based on the 2013 curriculum had not run optimally and students had not been trained to do non-routine questions. Therefore, a learning model was needed that can improve students' mathematical problem solving abilities, namely the Probem Based Learning (PBL) model. The PBL model is a learning model that begins with real problems developed from the knowledge already possessed. PBL is carried out in groups and students exchange ideas in completing the questions given. This model was expected to overcome students' mathematical problem solving abilities. This study aimed to determine how the application of the PBL model in learning in class X MIPA SMA Negeri 2 Padang. The results of the study show that students' mathematical problem solving abilities using PBL are better than conventional learning. The real level used is 0.05. So, it can be concluded that PBL can improve students' mathematical problem solving abilities.Keywords— Problem based learning, problem solving, real problems